Analisis Kekuatan dan Desain Frame Mini Bike 20 Inch menggunakan Pendekatan Finite Elemen Method (FEM) - Fariz Luthfi Nurulhadi; Rizal Hanifi; Oleh Oleh (Jurnal Ilmiah Wahana Pendidikan, 2022)
The bicycle is a means of transportation that has two wheels and originated in France since the early 18th. One type of bicycle that is currently popular is a mini bike. Mini bike users mostly come from teenagers to adults, especially men who use mini bike to take part in mini trek events or straight-line races. This is because the mini bike is very easy to modifty its speed performance. In addition, the mini bike has a variety of frame materials ranging from hi-teen steel, chromoly, alloy, carbon fiber, and titanium. The result of this study are an analysis of the loading of the equilibrium moment on the Mini Bike Frame, the coordination point of the center of gravity on the Mini Bike, has an axis value of Xo = 736,36mm and Yo = 455,06mm of Gravity, against (x-coordinate axis on the ground) equals the safer. The biggest moment that occurs due to the rider’s load and the reaction stress of the Ray and Rby axes is 922.835,02N.mm2, the safety factor value on the 20 Inch Mini Bike frame is still said to be safe, with the safety result in the solidworks simulation of 1,974.